SOCIOLOGICAL STUDY ON THE ROLE OF IMPLEMENTING DINIYAH MADRASAH IN CHARACTER FORMATION - Muhammad Handoyo (LPPM STAI Muhammadiyah Probolinggo, 2020)
Madrasah diniyah provides a very essential role in the development of character education. The community plays an active role so that the presence of madrasah diniyah will further strengthen the religiosity education of children after receiving general education. Because in general, madrasah diniyah to support the lack of religious education that children get while attending school lessons. The purpose of this research is to describe the sociological studies of Madrasah diniyah in Indonesia. This research is a library research which takes several references from scientific journals.